2019
DOI: 10.1534/g3.119.400705
|View full text |Cite
|
Sign up to set email alerts
|

Genome ofSpea multiplicata, a Rapidly Developing, Phenotypically Plastic, and Desert-Adapted Spadefoot Toad

Abstract: Frogs and toads (anurans) are widely used to study many biological processes. Yet, few anuran genomes have been sequenced, limiting research on these organisms. Here, we produce a draft genome for the Mexican spadefoot toad, Spea multiplicata, which is a member of an unsequenced anuran clade. Atypically for amphibians, spadefoots inhabit deserts. Consequently, they possess many unique adaptations, including rapid growth and development, prolonged dormancy, phenotypic (developmental) plasticity, and adaptive, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 87 publications
(106 reference statements)
0
27
0
Order By: Relevance
“…To measure gene expression, we followed the general procedure described by Seidl et al (2019) for 3' RNA‐seq data. We began by trimming the 3' RNA‐seq reads to remove adapter and poly‐A contamination using BBDuk (B. Bushnell, https://sourceforge.net/projects/bbmap) with the parameters: ktrim=r k = 23 mink=11 hdist=1 tpe tbo qtrim=r trimq=6 ftl=12 maq=6.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To measure gene expression, we followed the general procedure described by Seidl et al (2019) for 3' RNA‐seq data. We began by trimming the 3' RNA‐seq reads to remove adapter and poly‐A contamination using BBDuk (B. Bushnell, https://sourceforge.net/projects/bbmap) with the parameters: ktrim=r k = 23 mink=11 hdist=1 tpe tbo qtrim=r trimq=6 ftl=12 maq=6.…”
Section: Methodsmentioning
confidence: 99%
“…We began by trimming the 3' RNA‐seq reads to remove adapter and poly‐A contamination using BBDuk (B. Bushnell, https://sourceforge.net/projects/bbmap) with the parameters: ktrim=r k = 23 mink=11 hdist=1 tpe tbo qtrim=r trimq=6 ftl=12 maq=6. Individual reads were then mapped to the S. multiplicata genome (Seidl et al, 2019) using STAR aligner (Dobin et al, 2013) with default parameters for the Lexogen Quantseq kit. We used bedtools genomecov (Quinlan & Hall, 2010) to generate bed coverage files at all nucleotide positions and performed peak discovery by using the “findpeaks” function in the R package “pracma” (Borchers, 2019) with the following parameters: nups=1, ndowns=1, zero="0," peakpat=NULL, minpeakheight=500,minpeakdistance=3000, threshold=0, sortstr=FALSE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… The phylogenetic relationship of the frogs is derived from the tree on AmphibiaWeb ( https://amphibiaweb.org ), and the divergence time scale shown at the bottom is based on times estimated using TIMETREE ( http://www.timetree.org ). The genome size of each frog was estimated in this study ( Glandirana rugosa ) and in previous studies of other groups: Denton et al (2018) Preprint ( Pyxicephalus adspersu s), Seidl et al (2019) ( Spea multiplicata ), Li et al (2019) ( Leptobrachium leishanense ), Hellsten et al (2010) ( Xenopus tropicalis ), and Session et al (2016) ( Xenopus laevis ). The assembled genome size of Rhinella marina was estimated to be in the range of 1.98–2.38 Gb ( Edwards et al, 2018 ), and the average of the range is shown here.…”
Section: Resultsmentioning
confidence: 94%
“…Loci that were identified as significantly different in each contrast (Dryad dataset: https://doi.org/10.5061/dryad.h9w0vt4fj) were then mapped to the S. multiplicata reference genome (Seidl et al., 2019) using the “very sensitive local” setting in Bowtie2 (Langmead & Salzberg, 2012). Following mapping, we identified candidate genes for phenotype and/or plasticity as those for which an outlier locus occurred within the gene itself or where an outlier mapped within 10 kb upstream or downstream of the gene.…”
Section: Methodsmentioning
confidence: 99%